(untitled) (Applied Biological Research, 2017)
Flaxseed is a rich source of polyunsaturated fatty acids containing about 80% total oil with a high quantity of ω-3-fatty acids as well asmineral content. The objective of present study was to estimate the effect of different processing treatments viz., roasting, defatting and combination of both on the functional and biochemical properties of flaxseed flour. Flaxseed grains were processed as full fat non-roasted flour, full fat roasted flour, partially defatted roasted flour and partially defatted non-roasted flour. The results revealed that partial defatting and roasting increased crude protein (34.0%), ash (5.57%), crude fibre (12.34%) and total phenol (301.25 mg 100 g-1) contents as well as antioxidant activity (92.3%) in flaxseed flour. However, crude fat (37.7%), free fatty acid (0.37%), peroxide value (2.95 meq kg-1), phytic acid (950.2 mg 100 g-1) and tannins (318.4 mg 100 g-1) were highest in full fat non-roasted flour. Water absorption capacity (2.25 gg-1), foam capacity (21.76%) and foam stability (84.6%) were higher in partially defatted roasted flour. Based on functional and biochemical parameters partially defatted roasted flaxseed flour was found best.